EXCESS POS-EXERCISE OXYGEN COMSUMPTION: A COMPARATIVE STUDY IN UNTRAINED SUBJECTS (Fiep Bulletin - online, 2015)
This study aims to evaluate the intensity and duration of the EPOC in endurance and resistance exercise, in untrained subjects. Five individuals had initially carried through a test with 8-12 maximal, for determination of the exercise load. The maximal heart rate was took from the prediction: HRmax = 220-age. Three evaluations had been made, in three different days, with interval of at least one week between them. Oxygen consumption was measured with a metabolic analyzer VO2000 immediately after the exercise (IA), 2h after, 4h and 24h after. The days of evaluation for each subject had been randomized: resistance exercise (ER), aerobic exercise (EA) and control situation. Average values for ER were 2,26±0,86(before exercise), 2,67±0,46(IA), 2,04±0,17(2hs), 2,38±0,23(4hs) and 2,25±0,26(24hs). Average values for EA were 2,85±0,66(before exercise), 2,95±0,48(IA), 2,74±0,65(2hs), 2,09±0,57(4hs) and 3,13±0,18(24hs). No significant difference could be observed. The time duration and intensity of exercise in this study, had not significantly modified the oxygen consumption.
Keywords: .